A-174 Diurnal Preference Relation to Need for Cognition and Cognitive Reflection. (30th August 2021) - Pizer, Jasmin H; Myers, Melissa A; Hawley, Nanako A; Harrell, Murphy N; Hill, Benjamin D
Abstract: Objective: This study evaluated the effect of individual differences in diurnal preferences on a problem-solving test of intelligence and a measure of a personality trait of how much someone enjoys thinking. Method: Archival data from 85 participants who had completed measures online were utilized in this study. The sample was 51.8% female, 71.8% Caucasian, and mean age was 19.5. Participants completed the Morningness-Eveningness Questionnaire (MEQ), Composite Morningness Questionnaire (CMQ), Cognitive Reflection Test (CRT), and Need for Cognition Scale-Short Form (NFC). Raw score totals were utilized. Diurnal preferences were later grouped for morning, evening, or in between based on published MEQ and CMQ cutoffs. Lower scores indicate evening types, and higher scores indicate morning types. Results: Scores on measures of diurnal preference were significantly positively related to NFC (MEQ r = 0.28, p = 0.011; CMQ r = 0.36, p = 0.001) meaning that morning types tend to enjoy effortful mentation more. Diurnal preferences were not significantly related to CRT performance. One-way ANOVA was performed with diurnal preferences as the group factor and NFC and CRT as dependent variables. Significant main effects were not found for MEQ and NFC nor MEQ and CRT. Significant main effects were found for CMQ and NFC F(2, 77) = 5.33, p = 0.007, but not for CMQ and CRT. Conclusion: These findings indicate that diurnal preference was not associated with performance on the problem-solving intelligence test used in this study. However, morning types appear to be higher for personality traits related to motivation to engage in thinking and would be expected to do better on some cognitive tests that demand more test engagement.